Results in the Latin America and Caribbean Region 2013, Volume 2 - World Bank (Washington, DC, 2014)
Delivering on results is a key to achieving our Latin America and Caribbean strategy. This publication presents some of the recent results achieved by the World Bank Group, our clients, and our partners in the Latin America and Caribbean Region. The stories reflect our effort to help clients solve their development challenges quickly and effectively by providing a suite of financing, advisory and convening services. This is a way to demonstrate results in increasing opportunities for all citizens in key development areas, share them with other countries facing similar challenges, and learn from them to innovate and improve further actions.